Current State of PCR-Based Epstein-Barr Virus DNA Testing for Nasopharyngeal Cancer. (14th March 2017) - Kim, Kelly Y.; Le, Quynh-Thu; Yom, Sue S.; Pinsky, Benjamin A.; Bratman, Scott V.; Ng, Raymond H. W.; El Mubarak, Haja S.; Chan, K. C. Allen; Sander, Miriam; Conley, Barbara A.
Abstract : Clinical studies have shown plasma Epstein-Barr virus (EBV) DNA level to be an independent prognostic biomarker for nasopharyngeal carcinoma (NPC). However, the proportion of NPC patients whose tumors are associated with EBV vary with geographic location, and there are a variety of assays for plasma EBV. To develop the level of evidence needed to demonstrate the clinical utility of plasma EBV DNA detection for NPC patients and encourage widespread adoption of this biomarker test in clinical laboratories, validated harmonized assays are needed. In 2015, the National Cancer Institute (NCI) convened a Workshop on Harmonization of EBV Testing for Nasopharyngeal Cancer, where experts in head and neck oncology and laboratory medicine addressed the limitations of currently available polymerase chain reaction–based EBV DNA quantitation assays and discussed strategies for advancing the development of harmonized EBV DNA assays and their appropriate clinical use. This article presents the key recommendations to direct future efforts in assay harmonization and validation.